2002
DOI: 10.1007/s00417-002-0529-0
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal triamcinolone acetonide as treatment of macular edema in central retinal vein occlusion

Abstract: Intravitreal injection of triamcinolone acetonide may be a therapeutic option for long-standing cystoid macular edema due to central retinal vein occlusion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
99
1
7

Year Published

2003
2003
2009
2009

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 189 publications
(115 citation statements)
references
References 5 publications
8
99
1
7
Order By: Relevance
“…6,7,[9][10][11][12][13][14][15][16][17][18][19] A disturbed balance of angiogenic and inflammatory cytokines has been reported to be associated with retinal vein occlusion, 20 and experimental investigations and clinical studies have suggested a temporary antioedematous and antiangiogenic effect of intravitreal triamcinolone in eyes with CRVO. 6,7,[9][10][11][12][13][14][15][16][17][18][19] The two major side effects of the intravitreal triamcinolone were a steroid induced increase in intraocular pressure and development of cataract.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…6,7,[9][10][11][12][13][14][15][16][17][18][19] A disturbed balance of angiogenic and inflammatory cytokines has been reported to be associated with retinal vein occlusion, 20 and experimental investigations and clinical studies have suggested a temporary antioedematous and antiangiogenic effect of intravitreal triamcinolone in eyes with CRVO. 6,7,[9][10][11][12][13][14][15][16][17][18][19] The two major side effects of the intravitreal triamcinolone were a steroid induced increase in intraocular pressure and development of cataract.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,[9][10][11][12][13][14][15][16][17][18][19] A disturbed balance of angiogenic and inflammatory cytokines has been reported to be associated with retinal vein occlusion, 20 and experimental investigations and clinical studies have suggested a temporary antioedematous and antiangiogenic effect of intravitreal triamcinolone in eyes with CRVO. 6,7,[9][10][11][12][13][14][15][16][17][18][19] The two major side effects of the intravitreal triamcinolone were a steroid induced increase in intraocular pressure and development of cataract. [21][22][23][24][25] In contrast, studies on intravitreal bevacizumab by Rosenfeld et al and other researchers showed an improvement in visual acuity, reduction in macular thickness, and only minor complications in patients with CRVOs, [26][27][28][29][30][31][32][33][34] so that intravitreal triamcinolone was rapidly exchanged by intravitreal bevacizumab for the treatment of CRVO.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, intravitreal injections of triamcinolone acetonide have increasingly been used as a treatment for these diseases such as exudative age-related macular degeneration, [1][2][3][4][5][6][7][8] diffuse diabetic macular oedema, [6][7][8][9][10][11] central retinal vein occlusion, 12,13 persistent pseudophakic cystoid macular oedema, proliferative diabetic retinopathy, 14 proliferative vitreoretinopathy, 15 iris neovascularisation, 16 chronic prephthisical ocular hypotony, 17 chronic uveitis, [18][19][20][21] and neovascular glaucoma. 22 Complications and side-effects of the intravitreal injection of triamcinolone acetonide include secondary ocular hypertension developing in about 50% of the eyes injected and leading to high intraocular pressure up to 60 mmHg with the need for antiglaucomatous filtering surgery in about 1% of the eyes; 23 infectious endophthalmitis in less than 1% of the eyes, if the injection was performed under sterile criteria in the operation room; and, because of the cataractogenic effect of steroids, a cataract that has eventually to undergo surgery.…”
Section: Introductionmentioning
confidence: 99%